New records of planktonic foraminifera in the Shuaiba Formation (Aptian Age), Mesopotamian plain, South of Iraq - Al-Shawi, Zain Alabdeen A.; Mahdi, Maher M.; Mohammed, Abbas H. (Iraqi Journal of Science, 2019)
Shuaiba Formation is an important formation in Iraq, because of their deposition in the important period during the geological history of Arabian plate. The study is focused on a number of selected wells from several fields in southern Iraq, despite the many of oil studies to Shuaiba Formation but it lacks to paleontological studies. Four selected wells are chosen for the current study, Zb-290, Ru-358, R-624, WQ1-353, the selected wells are located within different fields, these are Zubair, Rumaila and West Qurna Oil Fields. In this study fourteen species followed to genus Hedbergella were discovered for first time as well as three genera followed to genus Heterohelix in the Shuaiba Formation at the different oil fields, Hedbergella tunisiensis Range Zone is suggested biozone to the current study, the age of this biozone is Aptian, most of the other genera located within this zone.